1989
DOI: 10.1111/j.1445-2197.1989.tb01644.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Resection: Value of Operative Ultrasound and Ultrasonic Dissection

Abstract: Twenty‐five patients having a major liver resection at the austin hospital were reviewed, 18 of whom had their operation after 1986. The indications were for melastatic disease in 14, hydatid in six and primary tumour in five. There were no operative deaths. Dissection was performed with the cavitron ultrasound surgical aspirator (cusa) and peroperative ultrasound used in 18 and without in seven. Mean blood loss was 1.75 u in the cusa group and 6.5 u in the non‐cusa group (p > 0.05). It is concluded that inlra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In our series, intra‐ and postoperative mean blood transfusion requirements were lower (1.5 ± 2.7 units) as compared with previous reports 3,4,6,16,18. We believe that these improved results may be obtained by the systematic use of an ultrasonic dissector, which increases the safety of liver resection, with clear skeletonization of the portal structures and hepatic veins, which in turn, greatly reduces the risk of major hemorrhage without clamping 12,29,30. In several studies,4,31,32 the increase in aminotransferase levels after liver surgery has been attributed to the duration of vascular clamping, and has been shown to reflect ischemic injury to the liver.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In our series, intra‐ and postoperative mean blood transfusion requirements were lower (1.5 ± 2.7 units) as compared with previous reports 3,4,6,16,18. We believe that these improved results may be obtained by the systematic use of an ultrasonic dissector, which increases the safety of liver resection, with clear skeletonization of the portal structures and hepatic veins, which in turn, greatly reduces the risk of major hemorrhage without clamping 12,29,30. In several studies,4,31,32 the increase in aminotransferase levels after liver surgery has been attributed to the duration of vascular clamping, and has been shown to reflect ischemic injury to the liver.…”
Section: Discussionmentioning
confidence: 49%
“…3,4,6,16,18 We believe that these improved results may be obtained by the systematic use of an ultrasonic dissector, which increases the safety of liver resection, with clear skeletonization of the portal structures and hepatic veins, which in turn, greatly reduces the risk of major hemorrhage without clamping. 12,29,30 In several studies, 4,31,32 the increase in aminotransferase levels after liver surgery has been attributed to the duration of vascular clamping, and has been shown to reflect ischemic injury to the liver. Belghiti et al 20 showed, in a randomized trial, that liver ischemic injury, assessed by a postoperative rise in aminotransferase concentration, was less severe with intermittent clamping versus continuous clamping for comparable or even longer cumulative durations of inflow occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Unit of Hepato-pancreatic-biliary Surgery, 1 Haematology Department, 2 Anaestesiology Department, Miguel Servet University Hospital, Zaragoza (Spain) 3 Department of Biochemistry and Molecular Biology, Medicine School, Malaga University, Spain. Coordinator of G.I.E.M.S.A.…”
Section: Integrated Blood Conservation Programme To Minimise Blood Lomentioning
confidence: 99%
“…However, as shown in Figure 1 of Bui's paper, blood loss in the 31 patients operated between 1987–1990 seems to be substantially less than that of the 17 patients who underwent hepatic resection between 1980–1986. If the use of the cavitron rather than the learning curve accounts for this difference [3, 4], as can be presumed from data in Table 3, then these two sub‐groups might have been studied separately.…”
mentioning
confidence: 99%
“…An Australian report on major liver resections records an operative mortality of zero and a mean blood loss of 1.75 units for patients operated upon since 1986. 2 This indicates that the situation has changed considerably. Overseas reports from larger series have reported a zero operation mortality also."…”
mentioning
confidence: 99%